Carbon abatement strategies for a capital-constrained manufacturer considering cap-and-trade regulation - Kong, Panpan; Yuan, Pengpeng (Frontiers in Environmental Science, 2025)
Government regulations and financial constraints challenge companies’ carbon reduction efforts. This study examines a supply chain comprising a retailer and a capital-constrained manufacturer regulated by a carbon cap-and-trade policy. It develops three analytical modes: manufacturer-independent abatement, supply chain loose cooperation for abatement, and energy service company (ESCO) provided abatement. The study explores the optimal carbon reduction levels and patterns for manufacturers, as well as the optimal pricing strategies for supply chain members. Additionally, the extension explores a scenario where supply chain members collaborate closely to reduce emissions and provides a coordination mechanism. Key findings include: (1) Under high interest rates, manufacturers favor ESCO abatement over loose cooperation, with independent abatement being least preferred. (2) While loose cooperation enhances the low-carbon performance of products more effectively than the independent mode, it imposes greater financial pressure on manufacturers. (3) In the ESCO mode, financial burden decreases with higher carbon prices but rises with greater ESCO abatement efficiency. (4) When the abatement revenue-sharing ratio is below a critical threshold, increasing the ratio benefits both the manufacturer and retailer. However, higher carbon prices reduce firm profits while alleviating manufacturers’ financing pressure. (5) The two-part tariff contract developed in this study allows the unit abatement level and firm profits in the independent abatement mode to align with those in the closely cooperative abatement mode. Finally, our findings provide practical insights for government and business decision-makers from a low-carbon perspective.